2019
DOI: 10.1038/s41419-019-1904-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular IL-37 promotes osteogenic differentiation of human bone marrow mesenchymal stem cells via activation of the PI3K/AKT signaling pathway

Abstract: Interleukin (IL)-37, a pivotal anti-inflammatory cytokine and a fundamental inhibitor of innate immunity, has recently been shown to be abnormally expressed in several autoimmune-related orthopedic diseases, including rheumatoid arthritis, ankylosing spondylitis, and osteoporosis. However, the role of IL-37 during osteogenic differentiation of mesenchymal stem cells (MSCs) remains largely unknown. In this study, extracellular IL-37 significantly increased osteoblast-specific gene expression, the number of mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 57 publications
(75 reference statements)
2
56
0
Order By: Relevance
“…Meanwhile, LNC_000052 expression was positively associated with Icam1, a gene which inhibits osteogenesis 19 , and Medag, a gene which promotes adipogenesis 20 , indicating that LNC_000052 might affect BMSC differentiation. In the present study, LNC_000052 overexpression led to reductions in the viability, migration, and differentiation properties of BMSCs, which were consistent with PI3K-AKT pathway dysfunction 21 . Notably, the negative regulatory subunit of PI3K, PIK3R1, was predicted to be a positively co-expressed mRNA of LNC_000052.…”
Section: Discussionsupporting
confidence: 87%
“…Meanwhile, LNC_000052 expression was positively associated with Icam1, a gene which inhibits osteogenesis 19 , and Medag, a gene which promotes adipogenesis 20 , indicating that LNC_000052 might affect BMSC differentiation. In the present study, LNC_000052 overexpression led to reductions in the viability, migration, and differentiation properties of BMSCs, which were consistent with PI3K-AKT pathway dysfunction 21 . Notably, the negative regulatory subunit of PI3K, PIK3R1, was predicted to be a positively co-expressed mRNA of LNC_000052.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have emphasized the key role of the PI3K/AKT signaling pathway for all of the periods of osteogenic differentiation, maturation, and bone formation [38][39][40][41]. Not only chondrocyte differentiation would be impaired, but also longitudinal bone growth would be inhibited by blocking the PI3K/AKT signaling pathway [3,42]. With the activation of the PI3K/AKT signaling pathway, IL-34 switched the phenotype of Kupffer cells from M1 to M2 in vitro [43].…”
Section: Discussionmentioning
confidence: 99%
“…Bone defects or fracture nonunion, which is still no e cacious way for the treatment, being one of the most intractable clinical diseases for orthopedic surgeons [1,2]. Severe fracture, bone tumor ablation, debridement of a wide range of bone infections and congenital defects can lead to the failure of fracture healing [3]. Fracture healing is known as an intricate physiologic process that the vascularity at fracture site, mechanical environment, growth factors, scaffolds and mesenchymal stem cells (MSCs) coordinate spatially and temporally to work towards restoring bone structural integrity without scar formation [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that the PI3K/Akt signaling pathway contributes to excessive cell proliferation, migration, and invasion in RA-FLSs [88,89]. Bone marrow MSCs (BMSCs), play a key role in the healing of bone defects, has been applied for the treatment of RA via activation of the PI3K/AKT signaling pathway [90].…”
Section: Discussionmentioning
confidence: 99%